Economic Impact Analysis Versus Investment Analysis: Cast-Bike Frame Manufacturing from Recycled Aluminum Alloy - Akhyar Akhyar; Abdillah Imron Nasution; Ali Mulyagusdin; Masri Ibrahim (Jurnal Teknik Mesin Unsyiah, 2021)
This paper discusses the standard economic impact analysis (EIA) and investment analysis of bicycle frame innovation products from recycled aluminum alloy. An input-output (I-O) model is using to perform the EIA. The indicators used for the economic impact analysis are the number of companies that produce bicycles, the number of workers, the number of products per year for the production of cast-bike from aluminum alloy recycled. Regarding employment support in the bicycle industry sector, the discussion arises in Labor productivity in ASEAN. Bicycle frame innovation from recycled aluminum alloy is interesting to study. There are two advantages, such as a simple production process and the use of recycled materials. As a result, the selling value of bicycle products is cheaper than other bicycles. The cast-bike from the aluminum recycled production process is also discussed in detail, starting from the design, simulation of stresses caused by loading conditions, material availability, and the production process.